The selective adhesion molecule inhibitor Natalizumab decreases multiple myeloma cell growth in the bone marrow microenvironment: therapeutic implications - Podar, Klaus; Zimmerhackl, Alexander; Fulciniti, Mariateresa; Tonon, Giovanni; Hainz, Ursula; Tai, Yu-Tzu; Vallet, Sonia; Halama, Niels; Jäger, Dirk; Olson, Dian L.; Sattler, Martin; Chauhan, Dharminder; et al. (British journal of haematology, 2011)
Recent advances regarding the introduction of anti-adhesion strategies as a novel therapeutic concept in oncology hold great promise. Here we evaluated the therapeutic potential of the new-in-class-molecule selective-adhesion-molecule (SAM) inhibitor Natalizumab, a recombinant humanized IgG4 monoclonal antibody, which binds integrin-α4, in multiple myeloma (MM). Natalizumab, but not a control antibody, inhibited adhesion of MM cells to non-cellular and cellular components of the microenvironment as well as disrupted the binding of already adherent MM cells. Consequently, Natalizumab blocked both the proliferative effect of MM-bone marrow (BM) stromal cell interaction on tumour cells, and vascular endothelial growth factor (VEGF)-induced angiogenesis in the BM milieu. Moreover, Natalizumab also blocked VEGF- and insulin-like growth factor 1 (IGF-1)-induced signalling sequelae triggering MM cell migration. In agreement with our in vitro results, Natalizumab inhibited tumour growth, VEGF secretion, and angiogenesis in a human severe combined immunodeficiency murine model of human MM in the human BM microenvironment. Importantly, Natalizumab not only blocked tumour cell adhesion, but also chemosensitized MM cells to bortezomib, in an in vitro therapeutically representative human MM-stroma cell co-culture system model. Our data therefore provide the rationale for the clinical evaluation of Natalizumab, preferably in combination with novel agents (e.g. bortezomib) to enhance MM cytotoxicity and improve patient outcome.